Political Party Deliberation: Mechanism for Safeguarding Constituent Rights against Vacancies in House of Representatives Affected by Political Party Dissolution - Fauzia, Ana; Esfandiari, Fitria (Universitas Negeri Gorontalo, 2024)
The Indonesian Constitutional Court has the power to dissolve political parties. But this power has never really been used. This research aims is to examine the impact of the legal vacuum created by the collapse of political parties. The problems raised in this research are as follows: First, aspects of the legitimacy of political party management deliberations in filling the vacancies of members of representative bodies as an implication of the dissolution of political parties;.Second, the deliberation mechanism of political party officials should be analyzed as a legal reform to fill the vacant positions of members of representative bodies from disbanded political parties. The findings of this study take the shape of a notion concerning party management decisions offering their constituent votes to other political parties that do not reach the threshold for collecting votes to sit in parliament because they do not satisfy the parliamentary threshold.